PENGARUH REPUTASI KLINIK DOKTER GIGI TERHADAP REKOMENDASI DAN LOYALITAS PASIEN - Yuni Rahmilia (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
The purpose of this paper is to highlight the influence reputation of dental clinic torecommendations and patient loyalty..The objectives of this research was : (a) the positiveeffect of perceived value to customer satisfaction, (b) the positive effect of customer satisfactionto loyalty, (c) the positive effect of customer satisfaction to reputation, (d) the positive effectof customer satisfaction to recommendation, (e) the positive effect of reputation to loyalty, (f)the positive effect of reputation to recommendation, The design of this research applies aquestionnaire toward of patient as a customer in Dentist and Dentists dental clinic for testinghypothesis. Meanwhile the required data consist of five variables; perceived value, customersatisfaction, reputation, recommendation, and loyalty. The aggregate numbers of customerbeing respondent of the study are 100. Data analysis used in this research was consists ofSmart Partial Least Square Regretion as software. The result of this research conclude thatvariable of perceived value had a positive effect to customer satisfaction, variable of satisfactionhad a positive effect to loyalty, reputation, recommendation and variable of reputation had apositive effect to recomendation but reputation had negatif effect to loyalty.Keywords : Reputation, Recommendation, Loyalty